Comparison of Laparoscopic Appendectomy with Open Appendectomy with Respect to Surgical Site Infection - Mohammad Shoaib Khan, Imtiaz Ahmed Khattak, Tariq Jamil, Muhammad Saqib, Syed Aamer Hussain, Sarmad Younis, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The purpose of this study is to compare the incidence of wound infection in laparoscopic and open appendectomy. Study Design: A randomized, controlled study Place and Duration: In the Surgical department of Khalifa Gul Nawaz Medical Teaching Institute, Bannu and Ayub Teaching Hospital, Abbottabad for the duration from January 2021 to June 2021. Methods: In this study, 220 patients with the diagnosis of acute appendicitis were selected and divided randomly into two groups; OA group (open appendectomy) and LA group (laparoscopic) appendectomy. In both groups, the general anesthesia was given for appendectomy. The wound was examined on the 1st, 2nd and 3rd postoperative day, and then on the 7th and 14th day postoperatively and was scored conferring to the wound asepsis Score. The SSI and total wound asepsis score was calculated subsequently. Results: Total of 200 patients with acute appendicitis were selected. In laparoscopic appendectomy (LA); 22.0±7.85 years was the mean age and 24.12±9.08 years was the mean age in open appendectomy (OA) group. There were 70 men and 40 women in the LA group, and 50 men and 60 women in the OA group. The LA group has M:F ratio of 1.9: 1 in the and 1: 1.3 in the OA group. While 108 patients had no complications and surgical site infection were noticed in two patients only in the LA group, 98 patients in the OA group recovered and surgical site infection were seen in 12 patients. Conclusion: Laparoscopic appendectomy is a safer and better choice than open appendectomy which decreases postoperative complications significantly such as wound infections. Keywords: Open appendectomy, Laparoscopic appendectomy, Acute appendicitis and Surgical site infection.